Yearbook Malmö Art Academy 1997-1998. - Douglas, Stan; Graham, Dan; Green, Renée; Hatton, Brian; Kremer, Mark; Ramberg, Lars; Robinson, Denise; Sandqvist, Gertrud; Malmö Art Academy, Mälmo (Malmö : Malmö Art Academy, 1998)
Andersson, Anna ; Andersson, Christian ; Andersson, Mats J. ; Attström, Maria ; Bertilsson, Andreas ; Brunström, Lars ; Bustnes, Maria ; Castro, Patricio Aros ; Curman, Christina ; Dahlberg, Jonas ; Djurberg, Nathalie ; Dyröy, Sigbjörn ; Ekman, Anna ; Forfang, Katrine M. ; Friberg, Ylva ; Gramstad, Else ; Gutke, Alexander ; Haugan, Dag-Are ; Hofwander, Fredrik ; Holmstrand, Leif ; Jeannin, Lisa ; Joannides, Gabriella ; Johansson, Ingegerd ; Johansson, Liselott ; Jordenö, Sara ; Josefsson, Sofie ; Kopp, Viktor ; Kromann, Elin Kristine ; Lennartsson, Nils Petter ; Lind, Jacob ; Lundstedt, Rikard ; Midhall, Cilla ; Mikkelsen, Emma ; Oldeman, Madelene ; Olsson, Oskar ; Ottertun, Magnus ; Pettersson, Petter ; Sarén, Lena ; Smed, Lotta ; Thierfelder, Magnus ; Walentin, Charlotte ; Wassman, Anna ; Winmalm, Nichlas ; Zetterlund, Pärnilla
Catalogus + appendix
Engels & Zweeds
boek